Fretting-corrosion behavior of electroless Ni-P/Ni-P-TiO2 coatings obtained on AZ91D magnesium alloy by a chromium-free process - Carrillo, Diego F.; Bermudez, Angela; Gómeza, Maryory A.; Zuleta, Alejandro A.; Castaño, Juan G.; Mischler, S. (ELSEVIER, 2020)
Ni-P electroless coatings are widely applied for protection of magnesium alloys and other materials due to the low energy consumption of the process and high resistance to corrosion and wear, properties that can be improved with the incorporation of particulate materials. Despite the attractive combination of properties of electroless coatings, studies in the tribocorrosion field, such as fretting-corrosion behavior of Ni-P electroless coatings, are very scarce. In this work, Ni–P-TiO2 composite electroless coatings with several variations on particles size and content applied on AZ91D magnesium alloys were analyzed under fretting-corrosion conditions in 3.5 wt.% NaCl. Coatings were obtained by direct electroless technique in multiple steps. Procedures were chromium-free and no activation pretreatment was needed. The tests were carried out using a fretting-corrosion tribometer from where open circuit potential and coefficient of friction were analyzed, as well as wear tracks on coatings surfaces were observed by SEM. The results obtained indicate that an improvement in the tribochemical behavior of Ni-P coatings can be achieved with the TiO2 codeposit, which modify the contact between body and counter body, the elastic accommodation and the dissipation of energy in the contact area

Los recubrimientos químico Ni-P se aplican ampliamente para la protección de aleaciones de magnesio y otros materiales debido a la bajo consumo energético del proceso y alta resistencia a la corrosión y al desgaste, propiedades que pueden mejorarse con la incorporación de materiales particulados. A pesar de la atractiva combinación de propiedades de Recubrimientos no electrolíticos, estudios en el campo de la tribocorrosión, como el comportamiento de corrosión por contacto de Ni-P no electrolítico. revestimientos, son muy escasos. En este trabajo, se utilizaron recubrimientos electrolíticos compuestos de Ni-P-TiO2 con varias variaciones en El tamaño y el contenido de las partículas aplicadas en aleaciones de magnesio AZ91D se analizaron en condiciones de corrosión por contacto en NaCl al 3,5% en peso. Los recubrimientos se obtuvieron mediante técnica directa no electrolítica en múltiples pasos. Los procedimientos fueron libre de cromo y no fue necesario ningún tratamiento previo de activación. Las pruebas se llevaron a cabo utilizando un método de corrosión por contacto. tribómetro desde donde se analizó el potencial de circuito abierto y el coeficiente de fricción, así como el desgaste de las pistas en Las superficies de los recubrimientos se observaron mediante SEM. Los resultados obtenidos indican que una mejora en la función triboquímica El comportamiento de los recubrimientos de Ni-P se puede lograr con el codeposito de TiO2, que modifica el contacto entre el cuerpo y contracuerpo, la acomodación elástica y la disipación de energía en el área de contacto
Keywords: Electricity; Electricidad; Tuberías de calor; Heat pipes; Electronic industries; Industrias electrónicas; Fretting-corrosion; Corrosión por contacto; Magnesium alloys; Aleaciones de magnesio; AZ91D; Composite electroless coatings; Recubrimientos compuestos no electrolíticos; Ni-P; TiO2